In a road of trying times: Unraveling the lived experiences of students in the new normal - Roselle Matammu Soriano; Marites Quibol Catabay; Michelle Gumiran Quijano (Institute of Advanced Engineering and Science, 2023)
The majority of educational systems worldwide have shifted to remote learning as a preventative strategy against the spread of coronavirus disease (COVID-19). This phenomenon is producing a lot of difficulties, as articulated by students in developing nations. Thus, this qualitative study sought to explore and understand the difficulties encountered by college students in Quirino State University in Philippines under the new normal of education. A total of 85 participants were purposely and conveniently selected to participate in an electronic survey through Google Forms. Further, to qualify and clarify responses from the respondents, the researchers conducted phone call interviews. The data were evaluated qualitatively using the NVIVO software. The findings revealed that the student’s difficulties in the new normal can be summed in 10 significant themes, namely: i) Vague module content; ii) Poor internet connectivity; iii) Lack of teacher’s guidance and motivation; iv) Financial problems;v) Stress/psychological pressure; vi) Insufficient learning materials; vii) Overloaded academic activities; viii) Conflict with household chores; ix) Personal factors; and x) Poor and inadequate learning environment. On the other hand, students’ coping strategies had four major themes, namely: i) Managing time wisely; ii) Having self-discipline; iii) Taking time for a break; and iv) Seeking help from others.